1993
DOI: 10.1038/366079a0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-ion pore behaviour in the CFTR chloride channel

Abstract: Cystic fibrosis transmembrane conductance regulator (CFTR) is a non-rectifying, low-conductance channel regulated by ATP and phosphorylation, which mediates apical chloride conductance in secretory epithelia and malfunctions in cystic fibrosis (CF). Mutations at Lys 335 and Arg 347 in the sixth predicted transmembrane helix of CFTR alter its halide selectivity in whole-cell studies and its single channel conductance, but the physical basis of these alterations is unknown and permeation in CFTR is poorly unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
258
6
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(284 citation statements)
references
References 19 publications
19
258
6
1
Order By: Relevance
“…Taken together, we have shown that the dimeric constructs of CFTR can be expressed in the plasma membrane of HEK 293 cells, and these CFTR dimers form functional chloride channels with unitary conductance of 8 pS, similar to the native CFTR channel (2,4). The gating properties of the wt-wt and ⌬R-⌬R channels are similar to the wt and ⌬R channels, whereas the wt-⌬R and ⌬R-wt channels exhibit mixed properties of the wt and ⌬R channels.…”
Section: A-s-l-v-p-r-g-s-g-g-g-g) As Shown Inmentioning
confidence: 87%
See 2 more Smart Citations
“…Taken together, we have shown that the dimeric constructs of CFTR can be expressed in the plasma membrane of HEK 293 cells, and these CFTR dimers form functional chloride channels with unitary conductance of 8 pS, similar to the native CFTR channel (2,4). The gating properties of the wt-wt and ⌬R-⌬R channels are similar to the wt and ⌬R channels, whereas the wt-⌬R and ⌬R-wt channels exhibit mixed properties of the wt and ⌬R channels.…”
Section: A-s-l-v-p-r-g-s-g-g-g-g) As Shown Inmentioning
confidence: 87%
“…The other possibility is that the 8-pS channel normally recorded in single channel measurements (2,4,5,14,17) actually represents dimeric complexes of CFTR that naturally assemble in the cell surface membrane. Data from the following sets of experiments support the latter hypothesis.…”
Section: Cftr As a Dimer 7628mentioning
confidence: 99%
See 1 more Smart Citation
“…Patch-clamp Studies of CL3 Mutants-Single CFTR channels were recorded from inside-out patches excised from stably expressing CHO cells, according to Tabcharani et al (1991) and Tabcharani et al (1993). Following patch excision, channels were activated by exposing the cytoplasmic face of the patch to 75 nM catalytic subunit of PKA (Promega) plus 1 mM Na 2 ATP.…”
Section: Methodsmentioning
confidence: 99%
“…Each of these residues was shown to be important in the Cl Ϫ conductance of the 9-pS pore of CFTR (16,17). In a previous report (18), we tested the hypothesis that insertion of arginine point mutations together could severely affect the Cl Ϫ conductance within CFTR.…”
Section: Single-channel Current Characteristics Of Cftr-mentioning
confidence: 99%